Effect of the TiO2 Nanocrystal Dispersion Over SBA‐15 in the Photocatalytic H2 Production Using Ethanol as Electron Donor. (15th July 2021) - Torres‐Garcia, Nidia L.; Fresno, Fernando; Oropeza, Freddy E.; Huirache‐Acuña, Rafael; de la Peña‐O'Shea, Víctor A.
Abstract: In this work, a series of TiO2 ‐based photocatalysts supported on mesoporous silica SBA‐15, which are synthesized with different wt% (10, 20, 40, 60, and 80) of TiO2, are studied. The catalysts are evaluated in gas‐phase H2 photo‐production using ethanol as an electron donor, observing changes in the hydrogen evolution with the TiO2 loading with an optimum charge of 20% w/w. In addition, the presence of Pt leads to a huge enhancement of the catalytic activity showing also a volcano plot behavior, the 20% w/w again being the best catalyst (895.9 µmol H2 gcat −1 ). This system also exhibits a high stability without a decrease in the production after 15 h. By means of different characterization techniques, it is possible to determine the interaction among the active phase, the metallic nanoparticle, and the catalytic support. These studies indicate that the use of mesoporous silica SBA‐15 as a support increases the dispersion of the active phase, resulting in an increase in the evolution rate of H2 . However, the lowest percentages of TiO2 give rise to amorphous TiO2 particles with high amount of superficial defects increasing the e − ‐h + recombination rate and decreasing the H2 production. Abstract : A series of TiO2 ‐based photocatalysts supported on mesoporous silica SBA‐15 are synthesized, thoroughly characterized and evaluated for gas‐phase ethanol photoreforming for H2 production, with an optimum charge of 20% w/w TiO2 . With Pt as co‐catalyst, 895.9 µmol H2 gcat −1 is obtained, without any deactivation after 15 h. The interactions between TiO2, platinum and SBA‐15 are determined.